An Evaluation of the Usefulness of Prosodic and Lexical Cues for Understanding Synthesized Speech of Mathematics. Issue 2 (3rd November 2016) - Frankel, Lois; Brownstein, Beth
Abstract: The work described in this report is the second phase of a project to provide easy‐to‐use tools for authoring and rendering secondary‐school algebra‐level math expressions in synthesized speech that is useful for students with blindness or low vision. This report describes the development and results of the second feedback study performed for our project, Expanding Audio Access to Mathematics Expressions by Students With Visual Impairments via MathML. That study focused on the use of certain prosodic and lexical elements in the ClearSpeak speech style and served as a basis for further refinements in that style's definition and implementation in the MathPlayer software. The primary parameters evaluated are students' success in drawing conclusions about the content and structure of certain math expressions and their perceptions regarding the helpfulness of the pace and wording of different text‐to‐speech renditions of the same or similar mathematical expressions. Please see Appendix A for information on obtaining a version of this report that is fully accessible using the tools described. Abstract : Report Number: ETS RR‐16–33